Understanding the process for developing sleep disorders among Japanese workers: a qualitative study - Ayako Toyoshima; Michiko Moriyama; Hidehisa Yamashita; Md Moshiur Rahman; KATM Ehsanul Huq; Yasmin Jahan; Kana Kazawa (Tabriz University of Medical Sciences, 2021)
Background: Sleep disorders have an enormous impact on occupational health and are counterproductive from an economic perspective. However, the processes of causing sleep disorders from psychosocial aspects have not yet been known. The purpose of this study was to describe how sleep disorders develop among workers with respect to different psychosocial conditions. Methods: A conventional qualitative content analysis was conducted with a semi-structured interview among twenty-seven workers (14 males and 13 females) who were diagnosed with sleep disorders or had a self-reported history of sleep difficulties. Study participants were recruited from a specialized clinic and communities using snowball sampling. This paper adhered to the Standards for Reporting Qualitative Research (SRQR) checklist. Results: The results showed that there were four steps involved in the sleep disorders development process. Firstly, participants with sleep disorders developed 'early warning signs' with 11 categories of triggers; secondly, 'aggravating factors' on top of these early warning signs; thirdly, workers tried to 'cope with' their sleep disorders in the ways they thought would be effective. Finally, when coping failed to improve the quality of sleep, it led to the onset of sleep disorders. Conclusion: The development of sleep disorders and triggers of psychosocial factors were revealed. An occupational health nurse can bring these findings in practice for preventing worker's sleep disorders.